Blind Adaptive Successive Interference Cancellation using Code-Constrained Constant Modulus Algorithms and Iterative Detection in Multipath Channels - de Lamare, R.C.; Sampaio-Neto, R. (Conference Record of the Thirty-Ninth Asilomar Conference onSignals, Systems and Computers, 2005, 2005)
In this work we propose blind adaptive successive interference cancellation (SIC) receivers with iterative detection for direct sequence code division multiple access (DS-CDMA) systems in frequency selective channels. A code-constrained constant modulus (CCM) design criterion based on constrained optimization techniques is proposed for SIC detectors in scenarios subject to multipath and computationally efficient blind adaptive stochastic gradient (SG) and recursive least squares (RLS) algorithms are described for estimating the parameters of SIC detectors. A novel iterative detection scheme that generates different cancellation orders and selects the most likely symbol estimate on the basis of the instantaneous minimum constant modulus (CM) criterion is also proposed. Simulation results for an uplink scenario assess the algorithms, the proposed blind adaptive SIC detectors against existing receivers and evaluate the effects of error propagation of the new cancellations techniques